CASE REPORTS AS AN ARTICLE: A FORLORN CAUSE? - Manas Bajpai (İstanbul Tıp Fakültesi Dergisi)
Case reports are defined as brief reports that describe the unique aspects of a medical case and contribute significantly to the existing medical literature and medical education. (1) The academic landscape has long been shaped by the publication of case reports, which have traditionally played a vital role in advancing scientific knowledge and understanding (2). Case reports, which provide detailed accounts of individual patient experiences, have been lauded for their ability to shed light on rare diseases, novel interventions, and unique clinical presentations (1). However, in recent years, there has been a growing concern about the declining importance of case reports in academia (2, 3).